PENGIMPLEMENTASIAN STANDAR KOMPETENSI LULUSAN DAN STANDAR ISI DI SD NEGERI 1 ABIANBASE - Ni Nyoman Yuli Suandewi; Ni Putu Yuliana Santini Putri (STKIP Subang, 2026)
This study aims to analyze the implementation of Graduate Competency Standards (SKL) and Content Standards (SI) at the elementary school level. The problem studied relates to how the integration between learning outcomes and classroom learning implementation affects student competency achievement. This study uses a qualitative approach with descriptive methods. Data collection was conducted through observation and documentation studies at SD Negeri 1 Abianbase. The results show that the implementation of SKL and SI has been implemented through integrated intracurricular, cocurricular, and extracurricular activities. However, its implementation has encountered several obstacles or barriers caused by many factors. The Independent Curriculum provides flexibility for schools to develop contextual and student-centered learning, thereby supporting the development of comprehensive competencies, including cognitive, affective, and psychomotor. However, improving teacher competency and institutional support is still needed for better and more consistent implementation.